Proceedings of the 4th ACM International Workshop on Experimental Evaluation and Characterization 2009
DOI: 10.1145/1614293.1614313
|View full text |Cite
|
Sign up to set email alerts
|

Interference mitigation in WiFi networks using multi-sector antennas

Abstract: Sectorized antennas provide an attractive solution to increase wireless network capacity through interference mitigation. Despite their increasing popularity, the real-world performance characteristics of such antennas in dense wireless mesh networks are not well understood. We demonstrate our multi-sector antenna prototypes and their performance through video streaming over an indoor wireless network in the presence of interfering nodes. We use our graphical tool to vary the sender, receiver, and interferer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…APs may be fitted with sensors to detect interference and switch channels automatically [1]. Using multi-sector antennas [13] and controlling data rates to avoid false backoffs can make the network more interference-resilient (although this is a trade-off since the lower data rates allow more noise-immune communication). Perhaps the most important insight is that there are many different non-Wi-Fi devices that may cause interference in Wi-Fi networks, and it is therefore important to understand and quickly adapt to the devices affecting the performance of the Wi-Fi channels.…”
Section: Discussionmentioning
confidence: 99%
“…APs may be fitted with sensors to detect interference and switch channels automatically [1]. Using multi-sector antennas [13] and controlling data rates to avoid false backoffs can make the network more interference-resilient (although this is a trade-off since the lower data rates allow more noise-immune communication). Perhaps the most important insight is that there are many different non-Wi-Fi devices that may cause interference in Wi-Fi networks, and it is therefore important to understand and quickly adapt to the devices affecting the performance of the Wi-Fi channels.…”
Section: Discussionmentioning
confidence: 99%
“…In general, we found that RF networks are exposed to a great source of noise produced by different elements, and these elements can have a significant impact on the interference level in the network [9]. Consequently, to keep the RF network performance, certain power levels are used to ensure signal links, but sometimes they generate more power than it is needed [5], [8]. In this paper, we are interested in determining the quality of the mobile RF signal coverage in an urban area, identifying the areas where the greatest power of RF signal is received.…”
Section: Presence Of Rf Signals In An Urban Environmentmentioning
confidence: 99%